A Static and Dynamic Analysis of Photovoltaic Penetration into MV Distribution Network - Maghami M.R.; Pasupuleti J.; Ling C.M. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Photovoltaic (PV) systems are becoming increasingly prevalent worldwide, particularly in power distribution networks. However, their intermittency and integration into distribution networks can have adverse effects. This study investigates the impact of large-scale solar integration into a typical Malaysian power grid network, focusing on voltage stability, short circuits, and power loss under peak and no-load conditions. Using Digsilent Power Factory software, static and dynamic power flow analyses were performed on a network consisting of two 132/11 kV transformers, an 11 kV busbar, and 112 loads served through eight feeders. Solar PV of 100 kW was integrated into each node, and the maximum allowable solar grid connection level was determined. The static results show that there were no violations in no-load conditions at 100 kW PV penetration. However, during peak load, there were violations at 0% PV penetration, but by increasing the level of solar grid connection to 60% (60 kW), the voltage level moves up to the acceptable range. Under contingency conditions, the results show that the minimum level of solar penetration is 80% (80 kW). The highest power loss occurs during peak time and is observed at 0% PV penetration. Feeder 8, the lounge feeder with the highest number of loads, is identified as the main cause of power loss. According to the short circuit analysis in peak and no-load conditions, the system experiences the highest shorts during peak loads. On the other hand, we conducted a dynamic simulation with load characteristics and compared the results for different levels of PV penetration. The results from the dynamic simulations show that lower limit violations occur even at 100% PV penetration for a brief period in all case studies. This study identifies the maximum permissible PV penetration as 125 kW. 2023 by the authors.